2015
DOI: 10.2135/cropsci2014.10.0706
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Boron‐Uptake Proteins in Roots are Correlated with Tolerance to Boron Stress in Barley

Abstract: Abbreviations: ELISA, enzyme-linked immunosorbent assay; NIP, NOD26-like intrinsic proteins; QTL, quantitative trait loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Surprisingly, most studies on nutrient uptake in plants were conducted only by changing the nutrient concentrations either to deficiency or toxicity levels. Only a few studies are available on the status of nutrient uptake proteins during abiotic stress [38,62,72,[77][78][79][80]. In all these studies, relative levels of the major nutrient-uptake proteins (NRT1, NRT2, AMT1, PHT1, BOR1, NIP5;1, and FRO1) per unit total root protein were quantified using ELISA (enzyme-linked immunosorbent assay) or Western blots [62,72] using protein-specific antibodies.…”
Section: A Decrease In Nutrient Uptake During Heat Stress Is Related ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, most studies on nutrient uptake in plants were conducted only by changing the nutrient concentrations either to deficiency or toxicity levels. Only a few studies are available on the status of nutrient uptake proteins during abiotic stress [38,62,72,[77][78][79][80]. In all these studies, relative levels of the major nutrient-uptake proteins (NRT1, NRT2, AMT1, PHT1, BOR1, NIP5;1, and FRO1) per unit total root protein were quantified using ELISA (enzyme-linked immunosorbent assay) or Western blots [62,72] using protein-specific antibodies.…”
Section: A Decrease In Nutrient Uptake During Heat Stress Is Related ...mentioning
confidence: 99%
“…In all these studies, relative levels of the major nutrient-uptake proteins (NRT1, NRT2, AMT1, PHT1, BOR1, NIP5;1, and FRO1) per unit total root protein were quantified using ELISA (enzyme-linked immunosorbent assay) or Western blots [62,72] using protein-specific antibodies. Polyclonal antibodies were designed that were specific to conserved domains of certain nutrient-uptake proteins across species [62,72,77]. Of the above-mentioned seven studies, only one study reported a change in nutrient-uptake protein due to heat stress alone [38].…”
Section: A Decrease In Nutrient Uptake During Heat Stress Is Related ...mentioning
confidence: 99%